Role of tourism and hospitality business in economic development. (2023) - Thommandru, Abhishek; Espinoza-Maguiña, Marcos; Ramirez-Asis, Edwin; Ray, Samrat; Naved, Mohd; Guzman-Avalos, Magna
Abstract: Tourism is critical in creating goodwill among people and, as a result, socioeconomic growth in the country. Tourism as an industry contributes significantly to the country's foreign exchange reserves and provides direct and indirect job possibilities to a broad segment of the population. Furthermore, supporting a nation's handicrafts and fine arts aids in the preservation of nature's beauty, cultural legacy of the country, and soil tradition, as well as strengthening the process of national integration and global brotherhood. For analytical purposes, it is important to distinguish between different forms of tourism. For example, tourism is often divided into two main categories: international tourism and domestic tourism, which is determined by the tourist's permanent residence's territorial limit. There is no minimum duration of travel required to qualify as a tour, and the important component is the movement away from the permanent residence to the destination or locations that are not in the same region. This article discusses the importance of tourism and the hospitality industry in economic growth.